Decolonizing through poetry in the Indigenous prairie context - Minor, Michael (2016)
Many important developments have followed from the distinction being made between post-colonial and settler-colonial situations. This distinction has had implications that reach across disciplines, but have especially impacted the immerging field of Indigenous studies in Canada, which had previously been drawing, and to a certain extent continue to draw, on theories from post-colonial studies. I write this at the intersection of Indigenous studies and English literature building on the theories of decolonization in settler-colonial situations. I show that English poetry written by people in the Indigenous prairie context is one particularly active site of decolonization, in the sense that scholars such as Linda Tuhiwai Smith explain. Through the poetry of Louise Halfe, Duncan Mercredi, Gregory Scofield, Marie Annharte (Née Baker) I show how important elements of Indigenous culture are being translated into printed poetry. Furthermore, these poets are Indigenizing aspects of settler-colonial culture. I use Halfe’s poetry, especially her collection Bear Bones & Feathers, to show the ways in which Indigenous concepts of medicine can be translated into printed poetic form and bring healing for the injuries inflicted by colonialism. Scholars Jo-Ann Episkenew and Sam McKegney provide other examples of this practice and the theoretical underpinnings for literature operating as medicine. Mercredi’s poetry reveals that some of the oral character of Indigenous stories can be translated into poetry. Indigenous scholars such as Neal McLeod argue that Indigenous cultures have long engaged in the use of wit and metaphor that is so prolific in poetry. Scofield translates ceremony into poetry. Drawing in part on J.L. Austin’s notion of performativity, I show that Indigenous poetry is an active force within communities. I read Annharte’s poetry as an example of Indigenization and activism in which she destabilizes the authority of the English language. Francis challenges artistic genres to assert his own Indigenous ...